Interface between EJA and Special Education: the teacher and the inclusion of young people and adults with intellectual disabilities - Mariele Angélica de Souza Freitas; Juliane Ap. de Paula Perez Campos (Arizona State University, 2014)
This study aimed to understand the scope of teaching practices and working conditions of an adult education teacher of students with intellectual disabilities enrolled in evening special education programs at the elementary schools.  The study was qualitative in nature, with characteristics of case study methodology. Data for the study were derived from semi-structured interviews, which respond adequately to our research goals. Results of the analysis point to the precarious work conditions of teachers of adult education and how this instability involves the organization and planning of curricula for students, including those with intellectual disabilities.